Hardware Based Genetic Evolution of Self-adaptive Arbitrary Response FIR Filters - Zarar, Shuayb; Mahammad, Noor; Veezhinathan, Kamakoti (ACM Journal of Applied Soft Computing (JSOC), 2011)
This work presents a hardware implementation of an FIR filter that is self-adaptive; that responds to arbitrary frequency response landscapes; that has built-in coefficient error tolerance capabilities; and that has a minimal adaptation latency. This hardware design is based on a heuristic genetic algorithm. Experimental results show that the proposed design is more efficient than non-evolutionary designs even for arbitrary response filters. As a byproduct, the paper also presents a novel flow for the complete hardware design of what is termed as an Evolutionary System on Chip (ESoC). With the inclusion of an evolutionary process, the ESoC is a new paradigm in modern System on Chip (SoC) designs. The ESoC methodology could be a very useful structured FPGA/ASIC implementation alternative in many practical applications of FIR filters.